Development Strategy of Kampung Namatota Tourist Attraction in Kaimana District, Kaimana Regency, West Papua Province - Juliana, Asima; Revida, Erika; Marjono, Ari; Purba, Sungkunen (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The development of historical tourism is one way of preserving cultural areas in the Kaimana District. The location of the research study on the development of historical tourism in the Kaimana District of Kaimana District is a tourist attraction of the Kingdom of Namatota, which is located in the village of Namatota. Because the location of the tourist location is far from the centre of the city, the minimum means and facilities of tourism support and promotion are sufficient so that the tourism of Namatota Village is less than maximum. This research aims to identify the factors that influence the attractiveness of tourists and the availability of means and infrastructure that exist for the historical tourist objects in the Kaimana district of Kaimana, as well as to draw up a plan for the development of historical tourist attractions in Kaima district. The research method used in this writing uses a qualitative approach to identify the factors that influence the interests of visitors, analyse what strengths and potential can be used as a development strategy, and identify weaknesses and threats that can hinder the development of the research site.his research uses the SWOT analysis method, which will produce the Development Strategy of Tourism Object Namatota, Kaimana District, West Papua Province. From the results of the analysis, it is concluded that the potential of historical tourist attractions is sufficiently high that it is potential to be developed, but the availability of support facilities and facilities is not sufficient, as is the development of natural and cultural potential accompanied by socialisation in the community. The strategies used can match the use of space in the tourist area and can also help preserve the environment. This research is expected to be a guideline for the government in developing the historical tourist area to maximise its development.